Retroperitoneal laparoscopic radical nephrectomy (RLRN) is associated with poor integrity of Gerota's fascia and perirenal fat: A prospective comparative study - Liu, Junyao; Zheng, Duo; Qi, Peng; Zheng, Xu; Zhang, Bin; He, Yang; Wang, Hongbo; Yue, Zhongjin; Wang, Zhiping; Shang, Panfeng (Frontiers in Surgery, 2023)
Purpose: To figure out the difference of integrity of Gerota’s fascia and perirenal fat between Retroperitoneal Laparoscopic Radical Nephrectomy (RLRN) and Transperitoneal Laparoscopic Radical Nephrectomy (TLRN). Methods: This is a prospective comparative study of patients with Renal Cell Carcinoma (RCC) from a designated tertiary center in Lanzhou, China. We have developed and propose a scoring tool to quantify the integrity of nephrectomy specimens from both approaches. The integrity score is based on 6 common conditions of nephrectomy specimens. Specimens are scored on a 1 to 6-point scale according to the integrity of Gerota’s fascia and perirenal fat. We applied the integrity score to 142 consecutive patients. Integrity scores were compared between RLRN and TLRN groups. Factors associated with low integrity score were assessed by logistic regression. Results: Among 142 patients, 79 (55.6%) patients and 63 (44.4%) patients, respectively, underwent RLRN and TLRN. There was a significant difference in the distribution of integrity score between the two groups (p < 0.001). RLRN (odds ratio 10.65, 95%CI 4.29-26.45, p < 0.001), tumor size (odds ratio 1.22, 95%CI 1.04-1.42, p = 0.015) and Body Mass Index (BMI) (odds ratio 0.83, 95%CI 0.72-0.96, p = 0.010) were significantly associated with low integrity score. The logistic regression equation showed good power to predict low integrity score. Conclusion: RLRN has poor integrity of Gerota’s fascia and the perirenal fat. The integrity score can be used to evaluate the extent of resection and specimen completeness in LRN. Postoperative evaluation of the integrity score is of great value for urologists to evaluate the risk of tumor residue.